Phototropins But Not Cryptochromes Mediate the Blue Light-Specific Promotion of Stomatal Conductance, While Both Enhance Photosynthesis and Transpiration under Full Sunlight - Boccalandro, Hernan Esteban (2011)
Leaf epidermal peels of Arabidopsis (Arabidopsis thaliana) mutants lacking either phototropins 1 and 2 (phot1 and phot2) or cryptochromes 1 and 2 (cry1 and cry2) exposed to a background of red light show severely impaired stomatal opening responses to blue light. Since phot and cry are UV-A/blue light photoreceptors, they may be involved in the perception of the blue light-specific signal that induces the aperture of the stomatal pores. In leaf epidermal peels, the blue light-specific effect saturates at low irradiances; therefore, it is considered to operate mainly under the low irradiance of dawn, dusk, or deep canopies. Conversely, we show that bothphot1 phot2andcry1 cry2have reduced stomatal conductance, transpiration, and photosynthesis, particularly under the high irradiance of full sunlight at midday. These mutants show compromised responses of stomatal conductance to irradiance. However, the effects of phot and cry on photosynthesis were largely nonstomatic. While the stomatal conductance phenotype ofphot1 phot2was blue light specific,cry1 cry2showed reduced stomatal conductance not only in response to blue light, but also in response to red light. The levels of abscisic acid were elevated incry1 cry2. We conclude that considering their effects at high irradiances cry and phot are critical for the control of transpiration and photosynthesis rates in the field. The effects of cry on stomatal conductance are largely indirect and involve the control of abscisic acid levels.